Analisis Pengaruh Fresnel Zone Terhadap Quality of Service Jaringan Komputer pada Teknologi Wireless - Ardhian Ahkim Miftahul Huda; Rissal Efendi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Fresnel Zone is defined as an elliptical-shaped indirect signal point position in the radio wave propagation path where the area is limited by indirect signals, so that it is tried to be kept unobstructed by obstacles. Precise Line of Sight (LOS) and Fresnel Zone calculations have a big influence on WLAN network design. Problems related to height differences and uneven topographic conditions and there are many obstacles in the tower area greatly affect the calculation of LOS and Fresnel Zone for Access Point (AP) placement. Placement of Access Points is a problem in network infrastructure, because improper placement of APs from site A to Site B will result in instability in Signal Strength, Transfer Rate, Bandwidth, Throughput, Packet Loss, Delay, and Jitter, causing user dissatisfaction in using the internet network. The difference in the results of obtaining the calculated QOS parameter values is influenced by the signal strength of each user, the greater the acquisition of signal strength, the better the acquisition of QOS parameters, so that the quality of computer network performance is getting better, different distances affect the signal strength obtained by the user, the farther the user's distance from the BTS, the higher the fresnel zone obtained. Thus, it should be noted that in designing a wireless infrastructure network, it must meet the requirements of Line of Sight (LOS) and a good Fresnel Zone so that the distribution of communication and information becomes more effective.